Constitution and public policies to eradicate gender-based violence in Spain: from the muses to the theatre - Ruiz González, José Gabriel (Universidad Nacional del Litoral, 2018)
The State Pact on Gender Violence, adopted in 2017 by the Spanish Parliament, contains the thesis ratified by the United Nations that violence against women is an abuse of human rights, reinforcing the status of the victim, by linking their Rights to constitutional values and oblige the State to guarantee them. This article, based on the Spanish normative framework, analyses the structuring instruments of the policies to be developed by he different administrations to determine whether, once the political consensus achieved in the year 2017 State Pact, there is an adequate framework for inter-administrative cooperation to eradicate violence against women.